AN ANALYSIS OF AUDITORY MANIFESTATIONS IN A GROUP OF ADULTS WITH AIDS PRIOR TO ANTIRETROVIRAL THERAPY - Khoza-Shangase, Katijah (African Journal of Infectious Diseases (AJID), 2011)
The chief objective of the current study was to investigate the auditory status in a group of adults with AIDS before commencing antiretroviral therapy (ART) in a hospital outpatient clinic in Gauteng, South Africa. A total sample of 150 participants, aged between 18 and 50 years, was assessed prospectively following a cross sectional qualitative research design. All participants underwent case history interviews and medical record reviews, otoscopy and tympanometry, as well as conventional pure tone audiometry testing. Descriptive statistics was used to analyse data obtained. Prevalence, type, degree, configuration, and symmetry of the auditory manifestations; as well as type of onset of hearing loss and the possible causes of the auditory manifestations were analysed. Findings indicated that auditory manifestations in adults with AIDS are heterogeneous in nature and are possibly due to various causes. Manifestations including hearing loss, tinnitus and vertigo (in varied combinations) were found; with the types of hearing loss being mainly sensorineural in nature. The severity of hearing loss ranged from mild to severe, occurred either unilaterally or bilaterally; with the type of onset being mainly gradual and progressive in nature. The varied causes of hearing loss included HIV infection or AIDS illness as a primary cause, opportunistic infections, and various ototoxic therapies that the patients had undergone. Implications for future research as well as future assessment and management of patients with AIDS are raised.